Economic Sovereignty of States - Chobanyan, G. (Bulletin of Yerevan University C: Jurisprudence, 2019)
The article is devoted to the issues of economic sovereignty in the frameworks of public international law. Particularly, the article addresses the historical evolution of the concept of economic sovereignty, then it represents the main elements of the contemporary economic sovereignty. The article discusses the internal and external aspects of economic sovereignty. Particularly, the author tried to address the issues on permanent sovereignty of a state over its natural resouses and economic activity. The author tried to show that the regulations of states in the field of foreign investments is one of the important issues in the realm of economic sovereignty of states. The author also underlines that all the states have equal economic sovereignty regardless of their economic strength.
Keywords: sovereignty, sovereign equality, economic sovereignty, permanent and natural resources, restrictions on foreign investments